SA NGAZA IN RELIGIOUS AND TRADITIONAL RITUALS PERFORMED BY THE NGADA ETHNIC PEOPLE IN FLORES - Banda, Maria Matildis; Kusuma, I Nyoman Weda; Ratna, I Nyoman Kutha; Pudentia, Pudentia (E-Journal of Cultural Studies; Volume 9, Number 4, November 2016, 2016)
This cultural study was conducted based on the primary data kasa’o (the traditional house bestowal of blessing) and wo’soDewa (the church bestowal of blessing).  The study was intended to reveal the elements causing the oral tradition Sa Ngaza (TLS) in the traditional ritual ‘ritual adat’ (RA) are still performed in the religious ritual ‘ritual keagamaan’ (RKA), the function and meaning of TLS in RA and RKA, how it has been inherited. The study used the theory of formula, the theory of semiotics, and the theory of practice, especially the practice of capital. The data were collected using the techniques of observation, interview, and documentation. Sa Ngaza is unique in regard to its pattern of formula in the same dimension in general and in the opening and closing formulas in particular. These formulas support the transmission of TLS, causing mori Sa Ngaza (the Sa Ngaza reporter) to be able to maintain the continuity of TLS and its growth in RA and RKA. The opening formula explains the identities of the characters. The thematic formula in RA and RKA reports different contents. TLS in RA emphasizes patadela (the ancestor’s massage); TLS in RKA emphasizes the Biblical massage. The meaning plurality in RA and RKA explains the acculturative relationship between the tradition and religion. In this relationship there is a shift in the identities of the characters, sa’o (the traditional house), and patadela . The hierarchy of leadership in the tradition and religion can save and hamper the oral tradition. Therefore, TLS can be generally inherited based on the role of leadership through families and society, religious institutions, and education.
Keywords: SaNgaza, kasa’o, Wo’oSa’oDewa, oral tradition of Sa Ngaza, traditional ritual, and religious ritual